Corrosion resistance of the ZnCr2O4 spinel in NaF-KF-AlF3 bath. (February 2018) - Li, Zhiyuan; Shi, Zhongqi; Zhang, Zhejian; Liu, Rongdi; Liu, Ying; Li, Jing; Qiao, Guanjun
Highlights: ZnCr2 O4 spinel processes excellent corrosion resistance in the NaF-KF-AlF3 electrolysis system. The corrosion rate of ZnCr2 O4 is calculated to be less than 0.028 cm/a. The reason for the excellent corrosion resistance of the ZnCr2 O4 is revealed. Abstract: ZnCr2 O4 was evaluated as a new sidewall material in the electrolysis of NaF19.69 -KF25.84 -(AlF3 )54.47 bath at 800 °C by both static and dynamic corrosion tests. The results showed that the composition and microstructure of ZnCr2 O4 were stable after the tests, and the ZnCr2 O4 possessed excellent corrosion resistance with the corrosion rate <0.028 cm/a, which was significantly lower than that of a common inert material NiFe2 O4 (1.2 cm/a). The outstanding corrosion resistance of ZnCr2 O4 can not only owe to the low electronegativity of Zn and Cr elements in the spinel structure, but also because of its thermodynamically stability under the chemical corrosion and reduction environments.